The role of community health workers in cervical cancer screening in low-income and middle-income countries: a systematic scoping review of the literature - James O’Donovan; Charles O’Donovan; Shobhana Nagraj (BMJ Global Health)
Introduction Community-based screening for cervical cancer and task sharing to community health workers (CHWs) have been suggested as a potential way to increase screening coverage in low- and middle-income countries (LMICs). The aims of the scoping review were to understand the following: (i) where and how CHWs are currently deployed in screening in LMIC settings; (ii) the methods used to train and support CHWs in screening, and (iii) The evidence on the cost-effectiveness of using CHWs to assist in screening.Methods A scoping literature search of 11 major databases and the grey literature was performed between 1978 and 2018. We included comprehensive search terms for ‘CHWs’ and ‘Cervical Cancer’, and used the World Bank criteria to define LMICs.Results Of the 420 articles screened, 15 met the inclusion criteria for review. Studies were located in Africa (n=5), Asia (n=5), and South and Central America (n=5). CHWs played a role in community education and raising awareness (n=14), conducting or assisting in cervical screening (n=5), or follow-up (n=1). 11 studies described CHW training activities. Only one study provided a formal cost analysis.Conclusion The roles of CHWs in cervical cancer screening in LMICs have largely to date focused on education, outreach, and awareness programmes. Community-based approaches to cervical cancer screening are feasible, although the sociocultural context plays an important role in the acceptability of these interventions. Further in-depth contextually grounded studies exploring the acceptability of such interventions are required, as well as studies exploring the cost-effectiveness of involving CHWs in cervical cancer screening activities.